Reliability and Concurrent Validity of the Situational Judgement Test for Evaluation of Strategic Thinking - Sooraksa, Nanta (Human Resource and Organization Development Journal, 2021)
This research aims to study reliability and concurrent validity of the situational judgement test for evaluation of employees’ strategic thinking. The research employed a quantitative method of data collection through situational judgement questionnaires with 540 responders comprised 255 managers and 285 employees in an automotive industry company. The findings revealed that 1) The test-retest results were positively correlated (r=0.945) deriving from a group of 64 responders in the pilot study. The retest was conducted in the period of 2 weeks apart from the test. This indicated that this test was consistent, stable, and highly reliable. 2) In studying the concurrent validity, there were significantly different of strategically thinking situational judgement test scores between managers and employees. Managers had a significantly higher strategic thinking than employees in each aspect and overall, at the 0.1 significant level. 3) Establishing a norm of scores test with using the Stanine Norm from 540 employees, the norm was able to classify the test scores into 3 groups: low, medium, and high strategic thinking groups. The findings indicated that this situational judgement test of strategic thinking can be applied to human resource management such as recruitment of employees and selection of employees and successors.